2007
DOI: 10.1109/tcapt.2007.903499
|View full text |Cite
|
Sign up to set email alerts
|

An Arc Study at High DC Current Levels in Automotive Applications

Abstract: International audienceIn order to fulfill the increasing electric power needs in automobiles and to satisfy new environmental requirements and security, the currently used 14 VDC electrical power systems must either supply higher currents (up to 100 A) or be changed to 42 V. Considering the difficulties of operating with this new 42 V system, we have focused our interests on higher currents by extending our previous 14 VDC study. The arc parameters such as break arc duration and extinction gap for different ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 9 publications
2
3
0
Order By: Relevance
“…The experiments show that the current minimum should reach around 100 A and then current reduction self-perpetuates (chopping value). This is in agreement with the previous studies that have shown that the arc voltage curve (in air) has inflection point at around 50 -150 A [11], and at lower currents the IV curve has negative slope leading to selfextinguishing property.…”
Section: Resultssupporting
confidence: 93%
“…The experiments show that the current minimum should reach around 100 A and then current reduction self-perpetuates (chopping value). This is in agreement with the previous studies that have shown that the arc voltage curve (in air) has inflection point at around 50 -150 A [11], and at lower currents the IV curve has negative slope leading to selfextinguishing property.…”
Section: Resultssupporting
confidence: 93%
“…8 shows the impact of different timing of Tch using zoomed curve for the gap voltage. The separation of contact occurs T0 =320 µs after the trip signal as seen by the gap voltage rise to around 30 V. This arc voltage is in broad agreement with the previous research [18]. Such arc voltage is adequate to commutate currents up to around 300-400 A with arc-only commutation [11].…”
Section: Experimental Testing a Hardware Set Upsupporting
confidence: 90%
“…There is abundant literature on arc voltage studies, both at low voltage [16] and high voltage [17], [18] applications. However, the commercial switches predominantly utilise single break point, while non-arcing disconnectors may employ multiple break points [14].…”
Section: A Break Points Connected In Seriesmentioning
confidence: 99%